Miteigentum an Grundstücken und einfache Gesellschaft Studie zur Koordination der Art. 646 ff. ZGB und Art. 530 ff. OR - Roth, Nicole (sui generis Verlag, 2021)
Although there is agreement that a pro rata entitlement is permissible in the simple partnership, the necessary interaction of Art. 646 ff. ZGB on co-ownership law and Art. 530 ff. OR on the law of the simple partnership is dealt with only rudimentarily. This is the point at which the work picks up, in that the two institutes of co-ownership and simple partnership are examined individually as well as in relation to their coordination possibilities in the case of real estate. The fundamental discussion of the legal institutions of co-ownership and simple partnership yields further insights of practical relevance. Thus, the delimitation difficulties between co-ownership and joint ownership as a result of simple partnership are also presented, general indications for the structuring of an agreed co-ownership arrangement are provided, and the concerns raised in the doctrine regarding pro rata entitlement in simple partnership are discussed.